2013
DOI: 10.1371/journal.pone.0073609
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Promote Tumor Growth and Metastasis via Direct Interaction between Aggrus/Podoplanin and CLEC-2

Abstract: The platelet aggregation-inducing factor Aggrus, also known as podoplanin, is frequently upregulated in several types of tumors and enhances hematogenous metastasis by interacting with and activating the platelet receptor CLEC-2. Thus, Aggrus–CLEC-2 binding could be a therapeutic molecular mechanism for cancer therapy. We generated a new anti-human Aggrus monoclonal antibody, MS-1, that suppressed Aggrus–CLEC-2 binding, Aggrus-induced platelet aggregation, and Aggrus-mediated tumor metastasis. Interestingly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(176 citation statements)
references
References 33 publications
5
168
0
1
Order By: Relevance
“…precisely, a new area may be opened in the development of drugs that specifically target the prometastatic activity of platelets such as CLEC-2/podoplanin, 45 TLR-4/HMGB1, 49 or ATX activity 39 without affecting their physiologic functions in hemostasis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…precisely, a new area may be opened in the development of drugs that specifically target the prometastatic activity of platelets such as CLEC-2/podoplanin, 45 TLR-4/HMGB1, 49 or ATX activity 39 without affecting their physiologic functions in hemostasis.…”
Section: Resultsmentioning
confidence: 99%
“…41 In addition, such incubation of tumor cells with washed thrombin-activated platelet membranes prior to injection in the mouse lateral tail vein lead to a significant increase in lung metastasis formation, confirming that priming tumor cells with platelet membranes 41 and interaction of C-type lectin-like receptor (CLEC)-2 with tumor-derived podoplanin. 45 Tumor cells secrete ADP that interacts with P2Y12, high-mobility group box1 protein 1 (HMGB1) that interacts with TLR-4 and express the tissue factor that activates the coagulation factors (VIIa/Xa) leading to thrombin production. All these factors mediate platelet activation and secretion of TGF-b.…”
Section: Platelets and Ctc Invasion/extravasationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such platelet-derived factors reportedly induce tumor vascular angiogenesis, growth, and epithelial-tomesenchymal transition (Italiano et al, 2008;Ho-Tin-Noé et al, 2009). Takagi et al showed the platelet aggregationinducing factor Aggrus, also known as podoplanin, was frequently upregulated in several types of tumors and enhanced hematogenous metastasis by interacting with and activating the platelet receptor CLEC-2 (Takagi et al, 2013). The development of platelet inhibitors that influence malignancy metastasis represents a promising area of targeted cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning platelets, specific surface receptors, such as C-type lectin-like receptor 2 (CLEC-2) (17), and the integrin αIIbβ3 (18)(19)(20) mediate interactions between platelets and tumor cells. Platelets also express other integrins, such as αvβ3 and 3 β1-containing integrins, namely α2β1, α5β1, and α6β1.…”
Section: Introductionmentioning
confidence: 99%